Hamas-Israel War: A Brief Analysis of First Two Phases of War - Bordas, Maria (European Scientific Journal, ESJ, 2024)
At the end of 2023, the Middle East experienced some new challenges. Among these new challenges, one of the most important of them all is the Hamas-Israel war. After almost four months of war and no end in sight, there are now growing questions about whether Israel will be able to accomplish its stated goals in Gaza. The brutality of the Hamas’s attack on October 7, the extent of the cruel massacre, shocked both the Israeli society and foreign public opinion. To better understand the factors of Hamas's operational success, the strategic surprise attack on Israel from Gaza, on October 7, 2023, needs a thorough analysis to understand all its political, intelligence, and operational failures aspects. It goes without saying that many elements of Hamas's brutal but largely successful attack are still unknown. Taking this into account, this paper focuses on only three elements of the ongoing war. Firstly, based on the qualitative methodology of research, this study evaluates and highlights the political background of the bloodiest attack in modern Israel's history which happened on October 7, 2023. Secondly, using the research methodology of data collection and analysis, this paper seeks to answer the still open-ended question, how was Hamas able to attack a country which operates one of the best intelligence organizations in the world by an extreme surprise? Finally, by using the narrative and historical models of qualitative research and the available data, this paper focuses on assessing the first and second phases of the war. Furthermore, the study formulates conclusions regarding the expected directions of change in the Israeli security system and some aspects of regional security implications of the ongoing Hamas-Israeli conflict. The potential result of the current paper is to present the reasons for the ongoing Gaza conflict based on the historical background. In addition, it provides a primary analysis, based on currently available information, of the first two phases of the obviously protracted Hamas-Israel conflict for the benefit of the community of researchers, scholars, and academics.